Psychological and Genetic Predictors of Pain Tolerance. Issue 2 (31st December 2018) - Patanwala, Asad E.; Norwood, Charles; Steiner, Heidi; Morrison, Daniel; Li, May; Walsh, Keith; Martinez, Marina; Baker, Sarah E.; Snyder, Eric M.; Karnes, Jason H.
Abstract : Previous studies have shown associations between genetic polymorphisms and pain tolerance, but psychological evaluations are seldom measured. The objective of this study was to determine the independent effects of demographic, psychological, and genetic predictors of cold noxious pain tolerance. Healthy subjects ( n  = 89) completed the Pain Catastrophizing Scale (PCS) and Fear of Pain Questionnaire (FPQ‐III), underwent genotyping for candidate single nucleotide polymorphisms (SNPs), and completed a cold‐pressor test in a 1–2°C water bath for a maximum of 3 minutes. The primary outcome measure was pain tolerance, defined as the maximum duration of time subjects left their nondominant hand in the cold‐water bath. Cox proportional hazards regression indicated that female sex, Asian race, and increasing PCS and FPQ‐III scores were associated with lower pain tolerance. No candidate SNP was significantly associated with pain tolerance. Future genetic studies should include demographic and psychological variables as confounders in experimental pain models.